Coagulation factors in chronic liver disease. Issue 2 (March 1969) - Donaldson, G. W. K.; Davies, S. H.; Darg, Alexis; Richmond, John
Abstract : Coagulation studies were carried out on 30 patients with chronic liver disease. The clotting defect was complex and involved factors V, VII, IX (Christmas factor), and prothrombin. Some patients showed a significant depression of factor IX in the presence of a normal one-stage prothrombin time. Thrombotest was found to be a good indicator of factor IX deficiency in this group of patients and may be of use as an additional liver function test. The screening of patients with liver disease for surgery or liver biopsy should assess the coagulation factors involved in both intrinsic and extrinsic thromboplastin generation.